SURGICAL TACTICS IN COMPLICATIONS OF GALLSTONE DISEASE IN PREGNANT WOMAN AT LATE STAGES OF GESTATION - M. A. Kitaeva; A. Yu. Korolkov; V. F. Bezhenar; D. A. Smirnov; D. N. Popov; S. F. Bagnenko (Вестник хирургии имени И.И. Грекова)
The objective is to analyze the results of rendering medical assistance to pregnant women delivered to the University clinic with suspicion of complications of cholelithiasis.Material and methods. The authors conducted the retrospective analysis of the case histories of pregnant women for 2 years, who applied urgently with suspicion of complications of cholelithiasis. In total, 69 patients at different stages of gestation, from 22 to 39 weeks of pregnancy, appealed with suspension of complication of cholelithiasis for this period. The average age of enrolled patients was 29.20±0.8 years. 48.98 % of the enrolled patients were pregnant at first time.Results. The presence of cholelithiasis was confirmed in 82.61 % of pregnant women. 43.86 % of these patients were diagnosed with hepatic colic, which was stopped by spasmolytic therapy. 52.63 % of pregnant women were diagnosed with acute cholecystitis. The surgical intervention – laparoscopic cholecystectomy - was required in 5.26 %. Acute biliary pancreatitis was in 8.77 % of pregnant women with cholelithiasis; delivery and revision of the abdominal cavity were required in 1 case. In addition, 3.51 % had choledocholithiasis with mechanical jaundice. All patients with this diagnosis were performed endoscopic papillosphincterotomy with lithoextraction.Conclusion. Complications of cholelithiasis rank the second place in the frequency of occurrence among urgent surgical diseases in pregnant women. The ultrasound examination is the starting point for determining the further treatment tactics for this category of patients. Pregnant women with complications of cholelithiasis should be examined in inpatient department of ambulance by surgeons and obstetrician-gynecologists collaboratively.